Analysis of Fair Price Valuation of Shares in Investment Decision Making in Islamic Banking Issuers on the Indonesia Stock Exchange (Years 2018-2021) - Mohammad Ibnu Hibban; Guntur Kusuma Wardana (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
In determining value (value) or commonly known as valuation, it has become mandatory for individuals or companies to express the value they have created. The main part of value extension in the valuation process is very necessary to be controlled by an investment analyst, this becomes important so that an investor can know what company has the potential to increase the value of the investment when investing. Moreover, the main goal of an investor is to seek profit or increase the value of what is invested. Therefore, the issue of value and investment decisions is an important thing to note for investors. The purpose of this study is to find out the fair value of Islamic banking shares on the Indonesia Stock Exchange so that it makes it easier to make investment decisions. From that background, this study was conducted with the title "Analysis of Fair Price Valuation of Shares in Investment Decision Making in Islamic Banking Issuers on the Indonesia Stock Exchange (2018-2021). This type of research is descriptive quantitative with a research sample of a number of three Sharia Bank companies listed on the Indonesia Stock Exchange in 2018-2021. The approach used is the method of calculating the price earning ratio (PER) and price to book value (PBV).From the results of the research shows that the investment decision that can be taken is if referring to the PER approach then we advise to buy shares in the company PT Bank Syariah Indonesia Tbk while on the PBV approach then we advise to buy shares in the company PT Bank Syariah Indonesia and PT Bank BTPN Syariah Tbk because the market value is still lower than its intrinsic value so that investors hope to achieve investment benefits from  increase in the difference in stock price.